2009 Reaccreditation: A Great Public University - Matthews, Nancy E. (My University, 2007)
Every 10 years, UW?Madison is reaccredited by the Higher Learning Commission of the North Central Association of Colleges and Schools. As part of the 2009 reaccreditation process, the university is conducting a self study called the 2009 UW-Madison Reaccreditation Project, which uses six strategic themes to help create a common vision for the next 10 years. Through this process, members of the reaccreditation team will look back at where the university has been and look forward to where it should go to continue to be a great public university. This update will provide a more detailed look into the engagement processes, the expected outcomes of the self study, and how it will be used to inform the next campus strategic plan.
Keywords: Leadership and Governance; Accountability, Autonomy, and Politics